Trilogy of sequential infections in a diabetic male. Issue 4 (18th November 2015) - Dogra, Vikas; Talwar, Deepak; Saxena, Rajat; Dabral, Charul; Joshi, Sharad; Bansal, Shobhit
Abstract: Uncontrolled diabetes is a known immunosuppressive state. It predisposes individuals to bacterial and fungal infections. The present case report demonstrates sequential infections by Klebsiella followed by tuberculosis and later development of mucormycosis in a poorly controlled diabetic patient. Timing of diagnosis is of essence because of high mortality seen with such pulmonary infections. High index of suspicion needs to be maintained as the same individual may harbor multiple infections as highlighted in this case. Abstract : Present case report demonstrates sequential infections by Klebsiella followed by tuberculosis and later development of mucormycosis in a poorly controlled diabetic patient.